Analysis of Heavy Metal Polution In River Mouths And Estuaries Tondano And Sario IN Manado City North Sulawesi - Sandra Tilaar (Sam Ratulangi University, 2014)
This study aims to determine the concentration of heavy metal Hg and Pb in estuary waters Tondano and Sario River in the Bay of Manado, and compare the state of the estuary waters Tondano with Sario estuary waters. Information obtained from this study is expected to be useful for the management of the marine environment, particularly coastal waters, so the environmental monitoring and utilization of coastal areas can be better implemented. The study was conducted for 4 months from September to December 2013. Analasis heavy metal analysis was performed according to the instructions better for Hg, Zn and Pb. The content of Hg and Zn in the water column in the estuary waters Tondano and Sario still within tolerable levels. The content of Pb in the water column in the estuary waters and estuary Tondano and Sario has passed the specified levels and has passed the tolerable levels. Human activity continues to grow around the Gulf waters of Manado so may result in appropriate changes that can lead to contamination, because it is necessary to monitor water quality regularly and continuously. Â Keywords: pollution, heavy metals, water quality Â A b s t r a k Penelitian ini bertujuan mengetahui konsentrasi logam berat Hg dan Pb pada Perairan Muara Sungai Tondano dan Sungai Sario di Teluk Manado, serta membandingkan keadaan Perairan Muara Sungai Tondano dengan Perairan Muara Sungai Sario. Informasi yang diperoleh dari penelitian ini diharapkan dapat bermanfaat bagi pengelolaan lingkungan perairan, khususnya perairan pantai, sehingga pemantauan lingkungan dan pemanfaatan wilayah pesisir pantai dapat dilaksanakan lebih baik. Penelitian dilakukan selama 4 bulan sejak bulan September sampai dengan bulan Desember 2013. Analasis logam berat dilakukan menurut petunjuk analisis baik untuk Hg, Zn dan Pb. Kandungan Hg dan Zn pada kolom air pada perairan Muara Sungai Tondano dan Muara Sungai Sario masih dalam kadar yang ditoleransi. Kandungan Pb pada kolom air di perairan Muara Sungai Tondano dan Muara Sungai Sario telah melewati kadar yang ditetapkan dan telah melewati kadar yang ditoleransi. Adanya aktivitas manusia yang terus berkembang di sekitar Perairan Teluk Manado sehingga dapat mengakibatkan terjadinya perubahan-perubahan secara tepat yang dapat mengakibatkan pencemaran, karena itu perlu diadakan pemantauan kualitas air secara berkala dan berkesinambungan. Â Kata kunci : pencemaran, logam berat, kualitas air